Kristin G.

# simplify each expression if f(x)=x2-1f(x-3)

I have to find and simplify each expression if f(x)=x2 -1

f(x-3)

f(4+h) - f(4)

## 3 Answers By Expert Tutors

By: Kathye P. answered • 10/02/12

Tutor
5.0 (150)

Math Geek, passionate about teaching Kathye P.

Oops, you're right! Thanks. I will correct it.

Report

10/02/12 Robert C.

Kathye, I really like your answers and your style of explaining things. There is a tiny arithmetic or typing error in one of your answers, I think:

"The second expression has two parts, and I will do the f(4+h) first:

f(4+h) = (4 + h)2 -1

Mutiplying and simplifying gives us: f(4+h) = h2 + 8h + 17"

That should be a 15, not a 17, right?

Report

10/02/12 Tamara J. answered • 10/02/12

Tutor
4.9 (51)

Math Tutoring - Algebra and Calculus (all levels) Robert C.

I like your answers Tamara. For the student's benefit, I will just show how that last one plays out.

"ƒ(4+h) - ƒ(4) = ((4+h)2-1) - ((4)2-1) = (4+h)2 - 16"

=(4 + h) (4 + h) -16

=16 + 8h + h2 -16

=8h + h2

=h(h+8)

Report

10/02/12

## Still looking for help? Get the right answer, fast.

Get a free answer to a quick problem.
Most questions answered within 4 hours.

#### OR

Choose an expert and meet online. No packages or subscriptions, pay only for the time you need.